2011
DOI: 10.1111/j.1365-2044.2011.06722.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative rewarming with Hot Dog® resistive heating and forced‐air heating: a trial of lower‐body warming

Abstract: SummaryResistive heating is an alternative to forced-air warming which is currently the most commonly used intra-operative warming system. We therefore tested the hypothesis that rewarming rates are similar with Hot Dog Ò (Augustine Biomedical) resistive and Bair Hugger Ò (Arizant) forced-air heating systems. We evaluated 28 patients having major maxillary tumour surgery. During the establishment of invasive monitoring, patients became hypothermic, dropping their core temperature to about 35°C. They were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
2
12
1
1
Order By: Relevance
“…As a method of rewarming patients who met hypothermic criteria at the start of the case, FAW was associated with a lower proportion of those patients that had a final temperature of <36°C (p = .023). This evidence is consistent with the work of Röder et al (2011) and Engelen et al (2011). Both of these studies found that the use of FAW to be superior to RHB when used as a means to rewarm hypothermic patients.…”
Section: Summary Of Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…As a method of rewarming patients who met hypothermic criteria at the start of the case, FAW was associated with a lower proportion of those patients that had a final temperature of <36°C (p = .023). This evidence is consistent with the work of Röder et al (2011) and Engelen et al (2011). Both of these studies found that the use of FAW to be superior to RHB when used as a means to rewarm hypothermic patients.…”
Section: Summary Of Findingssupporting
confidence: 89%
“…Active warming has been standard perioperative care for years as a means to prevent and treat inadvertent perioperative hypothermia (Hooper et al, 2010;NICE, 2008;Guiliano & Hendricks, 2017). Forced-air warming has been in use since the late 1980s with positive results well-documented in the literature (Hynson & Sessler, 1992;Röder et al, 2011, Engelen et al, 2011Hooper et al, 2010). Resistive-polymer heating blankets have gained in popularity in the temperature management of surgical patients and have also also been supported by the literature (Brandt et al, 2010;Nieh & Su, 2016).…”
Section: Generalizationsmentioning
confidence: 89%
See 2 more Smart Citations
“…4,36,43 Resistive polymer electric blankets have been demonstrated to be both equally and less effective compared with forced warm air blankets. 44,45 Forced warm air blankets can be placed over or under a patient with the direction of the air flow toward the patient. Circulating warm water pads and resistive polymer electric blankets can be placed over or under a patient as well; in addition, because of their flexibility, they can be wrapped around the patient.…”
Section: Active Techniquesmentioning
confidence: 99%